Summing up factorials (1)

Calculus Level 5

r = 0 ( r ! ) 2 ( 2 r + 1 ) ! = a π b b \sum_{ r=0 }^{ \infty }{ \frac{ { (r!) }^{ 2 } }{ \left( 2r+1 \right)! } } = \frac{ a\pi }{ b\sqrt{ b } }

If the above equation is true for positive coprime square-free integers a a and b b . Find the value of a + b a+b .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Jan 31, 2017

We have r = 0 ( r ! ) 2 ( 2 r + 1 ) ! = r = 0 Γ ( r + 1 ) 2 Γ ( 2 r + 2 ) = r = 0 B ( r + 1 , r + 1 ) = r = 0 0 1 x r ( 1 x ) r d x = 0 1 1 1 x ( 1 x ) d x = 0 1 1 x 2 x + 1 d x = [ 2 3 tan 1 ( 2 x 1 3 ) ] 0 1 = 4 3 tan 1 1 3 = 4 3 × 1 6 π = 2 π 3 3 \begin{aligned} \sum_{r=0}^\infty \frac{(r!)^2}{(2r+1)!} & = \sum_{r=0}^\infty \frac{\Gamma(r+1)^2}{\Gamma(2r+2)} \; = \; \sum_{r=0}^\infty B(r+1,r+1) \\ & = \sum_{r=0}^\infty \int_0^1 x^r(1-x)^r\,dx \; = \; \int_0^1 \frac{1}{1-x(1-x)}\,dx \; = \; \int_0^1 \frac{1}{x^2 - x + 1}\,dx \\ & = \Big[\tfrac{2}{\sqrt{3}}\tan^{-1}\left(\tfrac{2x-1}{\sqrt{3}}\right)\Big]_0^1 \; = \; \tfrac{4}{\sqrt{3}}\tan^{-1}\tfrac{1}{\sqrt{3}} \\ & = \tfrac{4}{\sqrt{3}} \times \tfrac16\pi \; = \; \tfrac{2\pi}{3\sqrt{3}} \end{aligned} making the answer 2 + 3 = 5 2+3=\boxed{5} .

Sangchul Lee
Mar 19, 2019

Notice that r ! = 0 t r e t d t = ( t = x 2 ) 0 2 x 2 r + 1 e x 2 d x . r! = \int_{0}^{\infty} t^r e^{-t} \, \mathrm{d}t \stackrel{(t=x^2)}{=} \int_{0}^{\infty} 2x^{2r+1}e^{-x^2} \, \mathrm{d}x. Using this, r = 0 r ! 2 ( 2 r + 1 ) ! = r = 0 1 ( 2 r + 1 ) ! ( 0 2 x 2 r + 1 e x 2 d x ) ( 0 2 y 2 r + 1 e y 2 d y ) = 4 0 0 r = 0 ( x y ) 2 r + 1 ( 2 r + 1 ) ! e x 2 y 2 d x d y = 4 0 0 sinh ( x y ) e x 2 y 2 d x d y = 2 0 0 ( e x 2 + x y y 2 e x 2 x y y 2 ) d x d y . \begin{aligned} \sum_{r=0}^{\infty}\frac{r!^2}{(2r+1)!} &= \sum_{r=0}^{\infty}\frac{1}{(2r+1)!}\left( \int_{0}^{\infty} 2 x^{2r+1} e^{-x^2} \, \mathrm{d}x \right)\left( \int_{0}^{\infty} 2 y^{2r+1} e^{-y^2} \, \mathrm{d}y \right) \\ &= 4 \int_{0}^{\infty}\int_{0}^{\infty} \sum_{r=0}^{\infty} \frac{(xy)^{2r+1}}{(2r+1)!} e^{-x^2-y^2} \, \mathrm{d}x\mathrm{d}y \\ &= 4 \int_{0}^{\infty}\int_{0}^{\infty} \sinh(x y) e^{-x^2-y^2} \, \mathrm{d}x\mathrm{d}y \\ &= 2 \int_{0}^{\infty}\int_{0}^{\infty} \left( e^{-x^2+xy-y^2} - e^{-x^2-xy-y^2} \right) \, \mathrm{d}x\mathrm{d}y. \end{aligned} The final integral can be computed with various tools ranging from brutal-force to multivariate normal distribution. Here, we will apply the polar-coordinates change. Substituting ( x , y ) = ( r cos θ , r sin θ ) (x, y) = (r\cos\theta, r\sin\theta) , r = 0 r ! 2 ( 2 r + 1 ) ! = 0 π / 2 0 2 r ( e r 2 ( 1 cos θ sin θ ) e r 2 ( 1 + cos θ sin θ ) ) d r d θ = 0 π / 2 ( 1 1 cos θ sin θ 1 1 + cos θ sin θ ) d θ . \begin{aligned} \sum_{r=0}^{\infty}\frac{r!^2}{(2r+1)!} &= \int_{0}^{\pi/2}\int_{0}^{\infty} 2r \left( e^{-r^2(1-\cos\theta\sin\theta)} - e^{-r^2(1+\cos\theta\sin\theta)} \right) \, \mathrm{d}r\mathrm{d}\theta \\ &= \int_{0}^{\pi/2} \left( \frac{1}{1-\cos\theta\sin\theta} - \frac{1}{1+\cos\theta\sin\theta} \right) \, \mathrm{d}\theta. \end{aligned} Substituting t = tan θ t=\tan\theta , r = 0 r ! 2 ( 2 r + 1 ) ! = 0 ( 1 1 t + t 2 1 1 + t + t 2 ) d t = 4 π 3 3 2 π 3 3 = 2 π 3 3 . \begin{aligned} \sum_{r=0}^{\infty}\frac{r!^2}{(2r+1)!} &= \int_{0}^{\infty} \left( \frac{1}{1-t+t^2} - \frac{1}{1+t+t^2} \right) \, \mathrm{d}t \\ &= \frac{4\pi}{3\sqrt{3}} - \frac{2\pi}{3\sqrt{3}} \\ &= \frac{2\pi}{3\sqrt{3}}. \end{aligned} Therefore ( a , b ) = ( 2 , 3 ) (a, b) = (2, 3) and their sum is 5 5 .

We can see that

r = 0 ( r ! ) 2 ( 2 r + 1 ) ! = r = 0 B ( r + 1 , r + 1 ) = r = 0 2 0 π 2 ( sin θ × cos θ ) 2 r + 1 d θ = r = 0 0 π 2 ( sin 2 θ ) 2 r + 1 2 2 r d θ = 0 π 2 r = 0 ( sin 2 θ ) 2 r + 1 2 2 r d θ = 0 π 2 ( sin 2 θ ) 1 ( sin 2 θ ) 2 2 2 d θ = 4 0 π 2 ( sin 2 θ ) 3 + ( cos 2 θ ) 2 d θ \begin{aligned} \sum_{r=0}^\infty \dfrac{(r!)^2}{(2r+1)!}& =\sum_{r=0}^\infty B(r+1,r+1)=\sum_{r=0}^\infty 2 \int_0^{\tfrac{\pi}{2}} (\sin\theta\times \cos\theta)^{2r+1} d\theta \\ & = \sum_{r=0}^\infty \int_0^{\tfrac{\pi}{2}} \dfrac{(\sin2\theta)^{2r+1}}{2^{2r}} d\theta =\int_0^{\tfrac{\pi}{2}} \sum_{r=0}^\infty \dfrac{(\sin2\theta)^{2r+1}}{2^{2r}} d\theta \\ & =\int_0^{\tfrac{\pi}{2}} \dfrac{(\sin2\theta)}{1-\dfrac{(\sin2\theta)^2}{2^2}} d\theta =4 \int_0^{\tfrac{\pi}{2}}\dfrac{(\sin2\theta)}{3+{(\cos2\theta)^2}} d\theta \\ \end{aligned}

let cos 2 θ = t \cos2\theta=t , then d t = 2 × s i n 2 θ d θ dt=-2\times sin2\theta d\theta

= 2 1 1 d t 3 + t 2 = [ 2 3 tan 1 ( t 3 ) ] 1 1 = 2 3 ( tan 1 1 3 tan 1 1 3 ) = 2 π 3 3 \begin{aligned} &=-2 \int_1^{-1}\dfrac{dt}{3+{t^2}} =\Big[\dfrac{2}{\sqrt{3}}\tan^{-1}\left(\dfrac{t}{\sqrt3}\right)\Big]_{-1}^1=\dfrac{2}{\sqrt{3}} \left( \tan^{-1}\dfrac{1}{\sqrt{3}}-\tan^{-1}\dfrac{-1}{\sqrt{3}}\right)=\dfrac{2\pi}{3\sqrt{3}}\\ \end{aligned}

Thus, a + b = 2 + 3 = 5 a+b=2+3=\boxed{5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...